2014
DOI: 10.5588/pha.14.0009
|View full text |Cite
|
Sign up to set email alerts
|

Preventable but neglected: rickets in an informal settlement, Nairobi, Kenya

Abstract: This study found that rickets is a common clinical presentation among children living in the informal settlement of Kibera and that there are likely multiple factors within that environment contributing to this condition. As rickets is a simply and inexpensively preventable non-communicable disease, we suggest that routine vitamin D supplementation be formally recommended by the World Health Organization for well-child care in Africa, especially in the contexts of informal settlements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…Another study on nutritional rickets in Kenya also reported on the most common clinical findings being swelling of the wrists (89%), frontal bossing (67%) and rachitic rosary of the chest (54%). 15 Thacher et al screened Nigerian children with rickets and found that there were five clinical features of rickets that independently predicted active rickets of which wrist and costochondral enlargement had the highest positive predictive values for active rickets which supports the clinical findings of this study. 16 Surprisingly in this study, 25(OH)D levels were found to be in the normal range (>50 nmol/L) in the majority of children with both types of rickets.…”
Section: • Saojsupporting
confidence: 77%
“…Another study on nutritional rickets in Kenya also reported on the most common clinical findings being swelling of the wrists (89%), frontal bossing (67%) and rachitic rosary of the chest (54%). 15 Thacher et al screened Nigerian children with rickets and found that there were five clinical features of rickets that independently predicted active rickets of which wrist and costochondral enlargement had the highest positive predictive values for active rickets which supports the clinical findings of this study. 16 Surprisingly in this study, 25(OH)D levels were found to be in the normal range (>50 nmol/L) in the majority of children with both types of rickets.…”
Section: • Saojsupporting
confidence: 77%
“…The finding that clinically defined rickets was associated with baseline stunting and wasting agrees with previous reports (H. L. Jones et al, 2015). In our study, clinical rickets cases were predominantly from urban sites as previously reported (Edwards et al, 2014;K. D. J. Jones et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The finding that clinically defined rickets was associated with baseline stunting and wasting agrees with previous reports (H. L. Jones et al, ). In our study, clinical rickets cases were predominantly from urban sites as previously reported (Edwards et al, ; K. D. J. Jones et al, ). Other studies, although not among children hospitalized with complicated SAM, have found evidence of association between vitamin D deficiency and severe pneumonia, gastrointestinal infection, and growth (Ganmaa et al, ; Haider et al, ; Muhe et al, ; Thornton et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings have been reported in two other studies of the MSF Kibera programme. 13,28 The high LFTU may be related to the transient nature of the inhabitants of Kibera: many have primary homes in rural Kenya and move between both residences during holidays and other times. Regardless, the lower LTFU among those PLHIV could suggest that routine defaulter tracing and counseling, only employed for this group, may lead to lower LTFU in the non-HIV group.…”
Section: Discussionmentioning
confidence: 99%